2012
DOI: 10.1007/s10877-012-9340-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pulse rate variability and heart rate variability in healthy subjects

Abstract: Both heart rate variability (HRV) and pulse rate variability (PRV) are noninvasive means for the assessment of autonomic nervous control of the heart. However, it is not settled whether or not the PRV obtained from either hand can be the surrogate of HRV. The HRV measures obtained from electrocardiographic signals and the PRV measures obtained from the pulse waves recorded from the index fingers of both hands were compared in normal subjects by using linear regression analysis and Bland and Altman method. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 28 publications
4
56
0
4
Order By: Relevance
“…PRV analysis has been performed in multiple studies using PPG signals recorded from the finger or earlobe and report varying levels of accuracy compared to HRV (2,4,5,7,8,15,21). By comparison to ECG signals, PPG waveforms are characteristically smooth and do not contain a clearly defined and detectable 'landmark' feature.…”
Section: Introductionmentioning
confidence: 99%
“…PRV analysis has been performed in multiple studies using PPG signals recorded from the finger or earlobe and report varying levels of accuracy compared to HRV (2,4,5,7,8,15,21). By comparison to ECG signals, PPG waveforms are characteristically smooth and do not contain a clearly defined and detectable 'landmark' feature.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed PRV using pulse oximetry due to the difficulty of collecting electrocardiography data in the MRI environment. Although PRV and HRV are highly correlated, particularly at rest (Hayano et al, 2005;Schäfer & Vagedes, 2013), the two measures rely on distinct physiological readouts of cardiac function and PRV may be less accurate for the measurement of high-frequency variability in particular (Wong et al, 2012). Much of the extant literature on PTSD and cardiac autonomic control assesses HRV and not PRV, (although some published "HRV" studies in fact utilize photoplethysmography; e.g., Minassian et al, 2015), and caution is warranted in generalizing the current results to the HRV literature until PRV is better established as an index of regulatory control and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [9] have shown that PRV obtained from a finger can be used as surrogate for HRV. However, Wong et al [7] reported the opposite finding and reported that it could be due to the pulse wave modification in the arterial system. Constant and colleagues [10] conducted a study on pulse wave recordings on the 3rd finger of the right hand, and showed that the PRV did not precisely reflect HRV in healthy subjects.…”
Section: Introductionmentioning
confidence: 97%
“…The morphology of the PPG signal is useful for the study of autonomic control of the peripheral vascular tone [5]. In fact, Wong et al [7] reported that the PPG signal might have an additional information in regards to cardiac autonomic tone compared to the ECG, because the peripheral vasculature is also modulated by the ANS. The physiological information derived from the R-R intervals can also be derived from the pulse-to-pulse (P-P) intervals of the PPG signal.…”
Section: Introductionmentioning
confidence: 99%